856 Sleep-writing, sleep-talking in uncontrolled REM-predominant obstructive sleep apnea. (3rd May 2021) - Ho, Minh Tam; Ghildiyal, Naomi; Liendo, Cesar; Monceaux, Brittany; Asghar, Sheila; Anne, Pratibha; Koothirezhi, Rupa; Okorie, Ugorji; Chernyshev, Oleg
Abstract: Introduction: Abnormal movements and behaviors during sleep are part of a larger group of nocturnal events that may occur during the sleep-wake cycle and/or the transitions into and out of sleep. We are presenting the case of OSA-related confusional arousals associated with sleep-writing and sleep-talking during REM-sleep. Report of case(s): 46 year old female with history of CAD, HTN, RLS, Anxiety, Depression, and REM predominant OSA (AHI of 2.9 per hour of sleep, REM AHI of 40 per hour of sleep, and oxygen saturation nadir of 91%), noncompliant with PAP therapy, returned to reestablish sleep medicine care and restart PAP therapy. The patient reported worsening of her OSA symptoms while being without PAP therapy. In addition to traditional OSA symptoms (snoring, frequent nighttime awakenings, restless legs, daytime sleepiness/fatigue), she reported episodes of sleep-talking, sleep-writing with demonstrated evidence of these events in her personal diary. She maintains a collective diary that incorporates her blood pressure readings, her weight loss accounts with records of meals in a day, as well as a separate log of letters that she will write and mail. In this diary, she has noticed sleep writing instances in each field, with no recollections subsequently on the act of writing them. The patient reported that these episodes of sleep writing would occur 3–4 times in a week, during this period of PAP noncompliance. Last reported instance of her sleep writing was October 2020. After re-initiation of PAP therapy, the patient has not reported further episodes of sleep-writing or sleep-talking. Conclusion: The sleep-writing is a very rare clinical symptom in the presentation of REM-predominant OSA as well as in REM/NREM parasomnias. We were not able to come across a case of it in the sleep literature review. Sleep-talking is a well-documented phenomenon. Confusional arousals may be responsible for symptoms of sleep-writing and sleep-talking in this case. We may repeat a sleep study with split protocol and parasomnia montage using AutoBipap if needed to investigate further. Further research should be done to explore the nature and correlation of sleep-writing in clinical practice. Support (if any): N/A